The role of negative intra-articular pressure in the maintenance of shoulder joint stability in dogs - Sidaway, B. K.; McLaughlin, R. M.; Elder, S. H.; Boyle, C. R.; Silverman, E. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The objective of this study was to evaluate the effect of negative intra-articular pressure on shoulder joint stability in canine cadavers. Cadaver forelimbs from 12 mature dogs were used. The forelimbs were placed in a testing frame and axially preloaded with 4 kg of weight. Shoulder joint stability was tested in flexion, extension, and neutral position before and after venting of the joint capsule. Humeral translation relative to the glenoid was induced by applying a 3 kg load in three different directions (cranial, lateral, and medial) and quantitatively measured by use of an electromagnetic motion tracking system. Peak translational data were compared in each joint position before and after venting of the joint capsule. After venting the shoulder joint capsule, a significant increase in translation was observed in the cranial direction with the joint in neutral position and in the medial direction with the joint in extension. The horizontal translations measured after venting of the joint capsule were likely not clinically relevant. Negative intra-articular pressure is not a major contributor to shoulder stability in dogs during weight-bearing.
Keywords: Shoulder joint; biomechanics; instability; intra-articular pressure; canine